Determination of Food Crops Contamination in Osun State, Nigeria Due to Radium-226, Thorium-232 and Potassium-40 Concentrations in the Environment - Chinyere Nwankpa, Alexander (European Journal of Sustainable Development, 2017)
One of the three goals of the United Nations for sustainable food security is to ensure that all people have access to sufficient, nutritionally adequate, and safe food. The south-west area of Nigeria especially Osun State is home to some of the most important minerals, which include bitumen, gold, kaolin, salt limestone, tantalite, coal and phosphate. As a result of the mineral occurrence, some parts of Osun State have become associated with significant levels of natural radioactivity. The exploration and exploitation of these minerals are known to have enormous consequences on the environment. This work is to measure the baseline radioactivity levels in some major food crops in Osun State and hence predict the potential radiological health effects. The study area (Osun State) has a total land mass of about 12820 km2, with a projected population of 5.1 million inhabitants. Osun State lies within latitudes 07o00 N and 08o25 N and longitudes 04o00 E and 05o11 E. Maize, Yam and cassava tubers that constitute the major food nutritive requirements were collected directly across farmlands in the State. The sampling locations were purposely chosen by considering the possibility of mineral resources, water resources, industry and farmlands. In order to have a total coverage of the study area, Osun State was divided into eight zones comprising the thirty local government areas in the State. Maize, yam and cassava were dried at room temperature until a constant weight was achieved. They were ground, homogenized and 250 g sealed in 1-liter Marinelli beaker and kept for 28 days in order to attain secular equilibrium before the gamma counting. The activity concentrations of Ra-226, Th-232, and K-40 were determined in the food samples using ?- ray spectrometry in the Centre for Energy Research and Development, Obafemi Awolowo University, Ile-Ife. The mean activity concentration of Ra-226, Th-232 and K-40 for yam were 1.72 ± 0.10 Bqkg-1, 2.24 ± 0.21 Bqkg-1 and 37.84 ± 2.40 Bqkg-1 respectively. The content of the radionuclides in maize gave a mean value of 2.49 ± 0.48 Bqkg-1 for Ra-226, 2.12 ± 0.06 Bqkg-1 for Th-232 and for K-40, the mean value is 30.92 ± 2.15 Bqkg-1 . The mean specific radionuclide concentrations in cassava is 2.00 ± 0.41 Bqkg-1 for Ra-226, 1.81 ± 0.12 Bqkg-1 for Th-232 and 40.35 ± 3.94 Bqkg-1 for K-40. The committed effective doses were 0.66 ?Svy-1 for the consumption of yam, 0.54 ?Svy-1 for maize, and 0.66 ?Svy-1 for cassava which are lower than the annual dose guideline for the general public. Therefore, the values obtained in this work show that there is no radiological contamination of foodstuffs consumed in Osun State. Keywords: Environment, Contamination, Minerals, Radioactivity, Committed Effective Dose.